Puberty timing associated with obesity and central obesity in Chinese Han girls - Qiguo Lian; Yanyan Mao; Shan Luo; Shucheng Zhang; Xiaowen Tu; Xiayun Zuo; Chaohua Lou; Weijin Zhou (BMC, 2019)
Abstract Background There is growing scientific evidence supports a link between increased childhood adiposity and early onset of puberty in girls worldwide in recent decades. However, the data from Chinese girls remain ambiguous. The aims of this study were to estimate the puberty milestones and examine attainment of puberty associated with obesity and central obesity in Chinese Han schoolgirls. Methods The cross-sectional school-based study examined 2996 Han schoolgirls aged 9 to 19 years from 6 provinces in China. Trained clinicians assessed  the girls for height, weight, waist circumference, Tanner stages of breast and pubic hair development, and menarcheal status. We classified girls as normal weight, overweight, or obese based on BMI, and as normal weight or central obese based on the waist-height ratio, then estimated and compared median age at a given Tanner stage or greater by weight class using Probit models. Results The median age at menarche was 12.36 years. The median ages at breast stages(B) 2 through 5 were 10.03, 11.38, 13.39, and 15.79 years, respectively, and at pubic hair stages(PH) 2 through 5 were 11.62, 12.70, 14.38, and 16.92 years, respectively. Girls from urban areas experienced menarche, B3 and B4 stages, and PH3 through PH5 stages earlier. Girls with central obesity and overweight/obesity reached puberty earlier at almost every Tanner stage of breast and pubic hair than normal girls. Girls with obesity developed PH2 and PH3 earlier than their overweight peers. However, we did not find any significant differences between girls with overweight and obesity at all stages of breast development. Conclusions Childhood obesity, including both overweight/obesity and central obesity, is associated with earlier attainment of puberty in Chinese Han schoolgirls.